Type IV collagen as marker of fibrosis in nonalcoholic liver disease - Alvina, Alvina (Universa Medicina, 2010)
Currently nonalcoholic fatty liver disease (NAFLD) and nonalcoholic steatohepatitis (NASH) are medical problems associated with the increasing prevalence of diabetes mellitus, obesity, hypertension and hypertriglyceridemia, usually designated as the metabolic syndrome associated with insulin resistance. One study demonstrated an increase in NAFLD prevalence of around 17-33% and in NASH prevalence of 5.7-16.5%. NAFLD comprises a range of mild to severe conditions, from simple steatosis to steatohepatitis, hepatic fibrosis and cirrhosis. The diagnosis of hepatic fibrosis is important for prognosis, stratification for treatment, and monitoring of treatment efficacy. Ultrasonography (USG) is a simple method for detecting fatty infiltrates in the liver. USG has a sensitivity of 82-89% and a specificity of 93%, but cannot differentiate between hepatic steatosis and fibrosis. The gold standard for evaluation of hepatic fibrosis is liver biopsy, which however is a painful and invasive procedure. Currently determination of serum type IV collagen has been suggested as an alternative to liver biopsy among the non-invasive methods for evaluation of hepatic fibrosis, as its serum concentration is closely correlated with advanced hepatic fibrosis in NASH. Type IV collagen is one of the components of basement membrane and its serum concentration is indicative of degradation of the extracellular matrix.